APPLICATION OF ELECTRICAL RESISTIVITY METHOD IN EVALUATION OF AQUIFER PROTECTIVE CAPACITY AND SOIL CORROSIVITY: A CASE STUDY OF WAJARI AND ENVIRONS, NORTHEASTERN, NIGERIA - YUSUF, A.; HARUNA, H.; TABALE, R. P.; MUKKAFA, S.; KWAMI, I. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Electrical resistivity technique was deployed in the study of extent of corrosivity and aquifer protective capacity (APC) or aquifer vulnerability of the overburden units around Wajari and environs, north eastern Nigeria. The objectives of this research includes; outlining areas that have high susceptibility to groundwater pollution from surface pollutants and subsurface soils that could be corrosive to buried metal pipes. Twelve (12) vertical electrical sounding (VES) locations were studied using electrode spreads of AB/2 equals to 80 m. OHMEGA Terrameter was deployed to acquire the data by employing Schlumberger array method. The analysis (interpretations) of the results were assisted by employing Win-Resist, Microsoft- Excel and surfer-13 Software The resistivity data interpretation revealed 4 geo-electric layers and the generated distribution curves are of type A, H, K, HK, and QQ. The measured thickness of the overburden lithologic units are in the range of 0.396 m to 27.2 m, with an average value of 5.407m. The longitudinal conductance of the overburden geologic units are in the range of 0.0199 mhos to 3934 mhos. VES 04 of the current study showed quite high topsoil resistivity signatures which is virtually non-corrosive (VNC). However, VES 08, 09 and 10 have moderate corrosivity and VES 01, 02, 03, 05, 06, 07, 11 and 12 are slightly corrosive. Five noticeable aquifer protective capacity zones were demarcated, on the basis of the obtained values of longitudinal conductance; namely poor (VES 03, 04, 05 and 08), weak (VES 01, 07 and 10), moderate (VES 02 and 06), very good (VES 09) and excellent (VES 11 and 12). VES 01, 03, 04, 05, 07, 08 and 10 of the research area could be susceptible to surface pollution whereas, VES02, 06, 09, 11, and 12 might not be susceptible to pollution due to the variation in the APC. Therefore, considering the planned siting of industrial park along this area (Gombe - Dadin Kowa route) by the Government of Gombe State. The results of this research shall form parts of the technical issues to be considered for groundwater, industrial, and infrastructural development planning of the area